The Concept of Incongruity in Comic Discourse: Linguocognitive Aspect. - Зубач, Оксана Адамівна (Луцький національний технічний університет, 2024)
Humour is an important background for the existence of the modern world, as it records important for society violations of various nature and creates the foundations for the formation of two content plans, which is the basis for the emergence of a comic effect at the linguistic and cultural level. It is not only a means of inducing positive emotions, but also a cognitive mechanism that uses the principles of formation of thinking and cognitive activity of a person of the target language culture. Its functional specificity consists in reducing or even overcoming the distance between knowledge about culture and language and their everyday life.